2018
DOI: 10.1088/1755-1315/153/6/062029
|View full text |Cite
|
Sign up to set email alerts
|

A review of pruning fruit trees

Abstract: Abstracts. The focus of this review is to present the results of studies and articles about ways to prune fruit trees. Pruning should be done in late winter or early spring so that the infection risk can be significantly decreased. This review will also offer an overview of methods to prevent infections and speed up recovery on the trees. The following is an interpretation of why high-power ultrasonic assisted pruning in the fruits trees is needed and will elaborate on the efficiency, labor costs, and safety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The study found that the indoor levels of particulate matter (PM 2.5 and PM 10 ) increased with an increase in humidity. An increase in humidity leads to an increase in the moisture in the air, and as a result the particles become moist and increase in size, reducing dispersion of the particles, leading to an increase in the concentration of the PM 2.5 and PM 10 in the air (26, 27). In contrast, the study revealed that an increase in temperature was associated with lower concentrations of PM 2.5 and PM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the indoor levels of particulate matter (PM 2.5 and PM 10 ) increased with an increase in humidity. An increase in humidity leads to an increase in the moisture in the air, and as a result the particles become moist and increase in size, reducing dispersion of the particles, leading to an increase in the concentration of the PM 2.5 and PM 10 in the air (26, 27). In contrast, the study revealed that an increase in temperature was associated with lower concentrations of PM 2.5 and PM 10 .…”
Section: Discussionmentioning
confidence: 99%
“…More trees are ruined or killed each year from improper pruning than other factors (Fickri & Siregar, 2018). It is crucial to understand that tree pruning nearly always forms injuries (Ow et al, 2013;Zhang et al, 2018). This would be set against the general belief, in many respects justified, that such work is good for trees.…”
Section: Guidelines Of Pruning Techniquementioning
confidence: 99%
“…At present, developing countries mainly use electric pruning shears [6] to achieve orchard pruning mechanization, but as litchi and longan trees are branch wood with high hardness that requires high strength to shear fibers [7,8]. In a high-intensity intensive working environment, given that the electric pruning shear head is squeezed and worn by the fibers and branches, the blades are often turned or chipped, which reduces the service life of the pruner and limits the pruning efficiency, hurting the application and promotion of orchard electric pruners [9][10][11].…”
Section: Introductionmentioning
confidence: 99%